Justification of the Annual Program of the Transport Company - Akhmet Murzagaliyev; Akzharkyn Balgynova; Alibek Murzagaliyev; Nurlybek Myrzabekov; Nurzhan Bakytzhanov (Automotive Experiences, 2023)
The issues of optimising economic and labour costs take a significant place in the production activities of transport companies. They depend on the socio-economic situation, objective reasons of production nature, availability of appropriate material and technical bases, as well as effective use and competence of enterprise management. It seems relevant to establish a transport enterprise programme to increase operational efficiency. Therefore, research outlines the characteristics of the work programme (order portfolios) of car service stations in the current environment and focuses on ensuring their stability. Mathematical modelling and methods of mathematical and statistical analysis served as principal tools, although analysis, synthesis, comparison and other methodologies were also significant. The authors represent the car service station production programme as the sum of failures and faults arriving at the enterprise in random order. The results of the experimental studies underwent analysis based on probability theory and mathematical statistics, where mathematical models of the annual programme and the probabilities of its distribution in a given time interval were obtained. The authors recommend measures to optimise the production programme by ensuring uniform loading of car service station structures. It can study numerous theoretical issues during the design phase of production sites and make accurate predictions. There are theoretical methodologies based on certain results, which are suitable for the design of road transport services. One of them is a calculation of the enterprise's annual program based on a grouping of the number of vehicles coming into the site. The work brings new regard to the shape of the programmes related to car service providers.